The Influence of the use Baby Walkers on Toddler Locomotor Skills in Singapore: 使用嬰兒學走路扶車對下肢大肌肉運動能力的影響 - TAN, Jernice Sing Yee; NONIS, Karen P. (Asian Journal of Physical Education & Recreation, 2008)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. Many studies have associated the use of baby walkers with rudimentary movement delays while studies on its influence on fundamental motor skills are limited. This study investigated the fundamental locomotor skills of 14 baby walker users (BWU, M Age = 49 months) with the Test of Gross Motor Development-2 (TGMD-2, Ulrich, 2000). The results showed significant differences in running and sliding. Further, that delayed rudimentary motor skills associated with the use of baby walkers do not continue into fundamental movement phase. 許多報吿顯示曾使用嬰見學走路扶車會影響下肢大肌肉運動能力。但針對兒童成長階段的資料卻有限。本報吿選用了第二代大肌肉運動能力測試工具(TGMD-2)探討十四位曾使用嬰兒學走路扶車的兒童(約4歲)。研究發現曾使用嬰兒學走路扶車的兒童在跑步和滑走有明顯的差異。但卻對他們的整體下肢大肌肉運動能力沒影響。這顯示曾使用嬰兒學走路扶車對大肌肉運動能力的負面影響不會連續到兒童成長階段。